2007
DOI: 10.1104/pp.107.102079
|View full text |Cite
|
Sign up to set email alerts
|

A Putative CCAAT-Binding Transcription Factor Is a Regulator of Flowering Timing in Arabidopsis

Abstract: Flowering at the appropriate time of year is essential for successful reproduction in plants. We found that HAP3b in Arabidopsis (Arabidopsis thaliana), a putative CCAAT-binding transcription factor gene, is involved in controlling flowering time. Overexpression of HAP3b promotes early flowering while hap3b, a null mutant of HAP3b, is delayed in flowering under a long-day photoperiod. Under short-day conditions, however, hap3b did not show a delayed flowering compared to wild type based on the leaf number, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 28 publications
5
125
2
1
Order By: Relevance
“…To systematically study the protein interactions of representative NF-Y subunits with RGA and CO, we selected two NF-YA (A1 and A2), three NF-YB (B1, B2 and B3), and three NF-YC (C1, C3 and C9) homologues because they are either relevant with flowering time control or expressed in the vasculature similarly to CO [28][29][30][31]34 . Yeast two-hybrid assays revealed that in addition to NF-YC3 and NF-YC9 found in initial yeast twohybrid screening, RGA also interacted strongly with NF-YA1 and NF-YA2, and weakly with NF-YB2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To systematically study the protein interactions of representative NF-Y subunits with RGA and CO, we selected two NF-YA (A1 and A2), three NF-YB (B1, B2 and B3), and three NF-YC (C1, C3 and C9) homologues because they are either relevant with flowering time control or expressed in the vasculature similarly to CO [28][29][30][31]34 . Yeast two-hybrid assays revealed that in addition to NF-YC3 and NF-YC9 found in initial yeast twohybrid screening, RGA also interacted strongly with NF-YA1 and NF-YA2, and weakly with NF-YB2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that photoperiod-dependent flowering involves nuclear factor Y (NF-Y) complexes, which are conserved combinatorial transcription factors in eukaryotes consisting of NF-YA, NF-YB and NF-YC subunits [28][29][30][31][32] . NF-Y and its binding element, the CCAAT box, are among the first set of trans-acting factors and cis-elements identified in eukaryotes 33 .…”
mentioning
confidence: 99%
“…Genome-wide analyses with loss-of-function mutants have confirmed FT as the major early target of CO (Wigge et al 2005). CO on its own does not bind DNA, but it likely acts as part of a CCAAT-box-binding complex involving HAP proteins (Ben-Naim et al 2006;Wenkel et al 2006;Cai et al 2007). CO is probably recruited to the FT promoter, based on experiments with an overexpressed version of CO that can be post-translationally controlled.…”
Section: Molecular Basis Of the External Coincidence Modelmentioning
confidence: 99%
“…These observations indicate that plant NF-Y subunits might act as general transcription factors, as in mammals (Yamamoto et al, 2009). Although a complete functional plant NF-Y complex has not yet been described, the individual subunits are known to be involved in a number of important physiological processes, such as specific developmental processes and response to environmental stimuli (Lotan et al, 1998;Kusnetsov et al, 1999;Miyoshi et al, 2003;Ben-Naim et al, 2006;Combier et al, 2006;Wenkel et al, 2006;Cai et al, 2007;Nelson et al, 2007;Warpeha et al, 2007;Siefers et al, 2009). A well-established example is the NF-YB subunit gene called LEAFY COTYLEDON-1 (LEC1), which specifically controls embryo development, especially the maturation phase.…”
Section: Gene Duplication Of Nf-y In Plantsmentioning
confidence: 99%